Overweight and Obesity in Adult Birth by Cesarean Section: A Systematic Review With Meta-analysis. Issue 2 (March 2023) - Chiavarini, Manuela; De Socio, Benedetta; Giacchetta, Irene; Fabiani, Roberto
Abstract : Context: Overweight/obesity is one of the most important health problems. Birth by cesarean section has been shown to influence long-term health outcomes including obesity. Objective: The aim of this systematic review-meta-analysis is to update acknowledgment of the increased risk of cesarean section on offspring's overweight/obesity. Methods: This study follows the PRISMA guidelines. A systematic literature search was conducted on Scopus, PubMed, and Web of Science; we have selected all the articles published until January 2, 2022. For inclusion, studies must have reported either (i) both birth by cesarean section and adult (≥18 years) offspring's body mass index; (ii) cohort or case-control study design; and (iii) a risk estimate. Heterogeneity testing was performed using Cochran's Q and I 2 statistics. Publication bias was assessed by the Egger test and the Begg test. Meta-analysis was performed through a random-effects model. Results: Twelve studies with a combined population of 180 065 subjects were included in the meta-analysis. The overall analysis (N = 19) yielded a combined risk estimate for overweight/obesity of 1.19 (95% CI, 1.08-1.30) and the test of heterogeneity resulted into Q = 57.44 ( I 2 = 68.67%, P ≤ .001). The risk of offspring obesity is 1.23 (95% CI, 1.09-1.39) and the test of heterogeneity resulted into Q = 39.55 ( I 2 = 69.66%, P ≤ .001). Children born by cesarean section have an increased risk of obesity in adulthood.